Autoimmune Encephalitis With Ganglionic a3-AChR Antibodies. (5th December 2022) - Zaid, Ghaida Khalaf; Saini, Chetan; Gachechiladzi, Leila; Salhab, Mahmoud
Abstract : Objective: To describe a case of autoimmune encephalitis presented as new onset refractory nonconvulsive status epilepticus and autonomic failure caused by alpha-3 ganglionic acetylcholine receptor autoantibodies (a3-AChR Ab). Background: Autoimmune autonomic ganglionopathy (AAG) is rare acquired dysautonomia in adults due to a3-AChR Ab. A patient typically presents with subacute autonomic dysfunction, and encephalitis has not been reported yet. Design/Methods: NA. Results: A 60 years old female presented with progressive worsening of mental status for two weeks. Vital signs were normal. The patient was somnolent, nonverbal, with tonic non-reactive pupils on the exam. CT head showed multiple subcortical hypodensities. MRI brain demonstrated T2-FLAIR hyperintense lesions in bifrontal lobes sparing the U-fibers, with abnormal leptomeningeal/pial perivenular type enhancement. MRI C/T spine, CT chest/Abd/pelvis were negative. Although serum and CSF testing showed inflammatory markers, meningoencephalitis and autoimmune encephalitis panel were negative, except for the serum Paraneoplastic panel was positive with high titer a3-AChR Abs. EEG showed nonconvulsive status epilepticus, which required management with three antiseizure medications. Initially, the patient had little response to empirical pulse methylprednisolone therapy. Later showed good clinical response with plasmapheresis. Later on she presented with nonobstructive small bowel obstruction, resolved with another pulse steroid therapy, discharged on dexamethasone taper. On a three-month follow-up, the patient was in near clinical remission, supported with resolved lesions on a repeat MRI. She never relapsed after two years of follow-up. Conclusions: Studies have shown that a3-AChR Abs can result in diverse neurological manifestations, mainly dysautonomia. Our patient presented with encephalitis, dysautonomia, and refractory nonconvulsive status epilepticus. Scans suggested diffuse leukoencephalopathy, patient was found to have high 3-ACHR antibody seropositivity. Initially, the patient was steroid-resistant but showed clinical improvement with plasmapheresis. We have described an interesting case of encephalitis likely associated with a3-AChR Ab that has not been previously described. More studies are required to confirm this association.